Methods and Models in Mammary Gland Biology and Breast Cancer Research - Englund, Johanna; Sumbalova Koledova, Zuzana (Journal of mammary gland biology and neoplasia, 2025)
The collection on Methods and Models in Mammary Gland Biology and Breast Cancer Research showcases recent advances in tools and models that enhance our understanding of mammary gland development and breast cancer. This collection includes sixteen articles, collectively addressing approaches to investigate key aspects of mammary gland biology and tumorigenesis, including hormonal signaling, tissue architecture, tumor microenvironment, and species-specific mammary development. The issue highlights innovations such as optimized progesterone receptor reporters, improved menopause models, and 3D-printed mammary epithelial structures. It also features advancements in organoid-based studies, in situ labeling of epithelial proliferation in large animals, preclinical models for breast cancer prevention, and high-resolution imaging techniques. Methodologies for studying macrophage-cancer cell interactions and lysosomal function are provided as step-by-step protocols. Additionally, review articles provide insights into diverse mammalian organoid systems, rat mammary tumor models, and strategies for modeling breast cancer metastasis. Together, these contributions advance mammary gland research by refining experimental approaches, expanding model diversity, and fostering translational applications in breast cancer.
Keywords: mléčné žlázy zvířat; Humans; Mammary Glands, Animal; Female; krysa rodu Rattus; lidé; zvířata; Mammary Glands, Human; Breast Neoplasms; ženské pohlaví; Organoids; Tumor Microenvironment; nádory prsu; organoidy; nádorové mikroprostředí; Rats; mléčné žlázy lidské; Animals; Disease Models, Animal; modely nemocí na zvířatech